## Explain what’s wrong with this solution process. 2 – 3(4 – 6) = -1(-2) = 2

Question

Explain what’s wrong with this solution process.

2 – 3(4 – 6)

= -1(-2)

= 2

in progress
0

Mathematics
1 week
2021-07-22T17:31:14+00:00
2021-07-22T17:31:14+00:00 1 Answers
5 views
0
## Answers ( )

Answer:You have to apply BODMAS

Step-by-step explanation:2-3(4-6)

=2-12+18

=8

Remember to either solve what’s in the brackets first or first multiply what’s outside the bracket to all numbers within the brackets (Like how I did)